AI-POWERED ANALYSIS OF BRAND-CONSUMER ENGAGEMENT IN THE DIGITAL ERA: INSIGHTS FROM INDIAN MILLENNIALS - Sharma, Tanushree; Jha, Shilpi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Brand-consumer interaction has changed into a dynamic and data-driven process in the fast-changing digital era. This is especially true for Indian millennials, who are tech-savvy and use social media a lot. Their brand loyalty habits are also changing. This research investigates how Artificial Intelligence (AI) can help us understand and predict how brand-consumer interaction trends will change in this group. The study uses a mixed-method research approach that combines social media analytics, polls, and data on how people connect with brands to get both numeric and qualitative information about involvement and behaviour. To look at big datasets, AI-powered methods are used. These include natural language processing (NLP) for figuring out how people feel about something, machine learning algorithms for guessing how engaged people will be, and grouping models for dividing people into groups based on their behaviour. The results show clear patterns of interaction that are affected by culture connection, content personalization, and brand trustworthiness. Personalized marketing strategies that use AI to create profiles of consumers lead to a big rise in involvement and brand loyalty, especially when they are tuned to people’s language tastes and living goals. Predictive models also show that real-time mood tracking lets brands change their campaigns on the fly, which makes customers happier and more loyal over time. The results have important implications for marketers who want to improve their digital efforts. They highlight the importance of AI in revealing complex customer behaviour and making hyper-personalized interaction strategies possible. This study adds to the growing amount of research on AI in marketing by looking at how to connect young consumers in India. It does this by closing the gap between using technology and communicating with brands in a way that is culturally relevant.